MOE ASPIRES TOWARDS PRODUCING BALANCED AND HOLISTIC GRADUATES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, 18 April 2015 “ We aspire to produce balanced and holistic graduates in various fields, with highlevel thinking skills and being competitive globally while still upholding the tenets of Rukun Negara.” This was stated by Education Minister II, Dato’ Seri Idris Jusoh in his speech, in conjunction with Majlis Anugerah Tokoh Siswa 2014 (ATS 2014) at the Dewan Utama, Engineering Campus, Universiti Sains Malaysia (USM), Nibong Tebal, here yesterday night.